Isolation and characterization of cyclodextrin glucanotransferase (CGTase) producing bacteria - 324077 Mohd. Khairizal Mahat; Rosli Md. Illias; Noraini Abd. Rashid; National Biotechnology Seminar (13th : 2001 : Melaka) ([s.l : s.n], 2001)
50